Modified passivity-based current controller design of permanent magnet synchronous generator for wind conversion system. (4th March 2022) - Belkhier, Youcef; Achour, Abdelyazid; Ullah, Nasim; Shaw, Rabindra Nath
ABSTRACT: Permanent-magnet synchronous generator (PMSG) associated with power electronics is a complex object to control due to the existence of nonlinearly coupled variables, and time-varying parameters. This paper presents a new passivity-based current controller (PBCC) design with flux orientation of a conversion system-based variable speed wind with PMSG connected to the grid through PWM converter with DC-Link. This technique is energy based and injects a damping term which ensures the stability and the convergence of the measured signals towards their references which forces the conversion system to operate at an optimal power point, to extract the maximum power produced. The main objectives of this study consist of two main parts: extract the maximum wind power through controlling the rotational of the PMSG and transfer this power to the grid-side converter, for this, a new controller is proposed. The second one is to maintain the DC-link voltage and the generated reactive power at their reference values, despite any possible constraints related to the machine-side converter (MSC), for this, a classical PI controller is investigated, that is to improve performances of the wind system. The obtained simulation results under MATLAB/Simulink address the high-performance and fast response of the proposed strategy.